Facts, intentions, questions: English ‘come-to-know’ predicates in deliberative environments - Anand, Pranav; Korotkova, Natasha (Proceedings of the Amsterdam Colloquium, 2024)
This paper explores a distributional interaction in English between (i) deliberative environ ments, e.g., intend; (ii) ‘come-to-know’ verbs (CtKs): factive change-of-belief verbs, e.g., discover and find out; and (iii) complement selection. We show that deliberative environ ments permit CtKs only when they embed questions. We derive this constraint from a clash between two presuppositions of CtKs, their factivity and change-of-state requirements, that emerges due to the projection properties of deliberative environments. We show that when the factivity presupposition is either absent (as with non-factive change-of-belief predicates) or accommodated locally, CtKs in deliberative environments permit declarative complements.